Solubilization Inclusion Bodies from Synthetic Recombinant PGA Gene Expressed in E. coli BL21(DE3) by Denaturing and Non-denaturing Agents - Purwanto Purwanto; Sismindari Sismindari; Indah Purwantini; Rumiyati Rumiyati; Muthi'ah Rasyidah; Muhammad Adi Mulia (Universitas Airlangga, 2024)
Background: With the rise in green chemistry, the synthesis of antibiotic compounds through enzymatic processes is a preferred option. Penicillin-G acylase (PGA) is an important enzyme for producing important antibiotics, such as penicillin and its derivatives. Therefore, studies on PGA have been conducted worldwide. In the penicillin biosynthetic pathway, PGA catalyzes the conversion of penicillin G into 6-amino penicillanic acid (6-APA), a precursor for the enzymatic synthesis of penicillin derivatives. Unfortunately, bacteria naturally produce PGA in small quantities. Objective: One strategy for producing this enzyme in large quantities is DNA recombination, which is expressed in Escherichia coli. The formation of inclusion bodies (IBs) is a common obstacle to protein overexpression in Escherichia coli. In this study, we discuss IBs solubilization methods for recombinant PGA derived from E. coli (rPGAEc) expressed in E. coli BL21 (DE3). Recombinant E. coli BL21 (DE3) cells harboring rPGAEc were induced with IPTG for enzyme expression. Induction was performed at 16 °C for 4 h and 24 h. The PGA enzyme expressed in the IBs form was then incubated in two solutions containing 8 M urea and 0.2% sarcosine to obtain a soluble enzyme. Results: Based on protein analysis by SDS-PAGE, a solution containing 8 M urea solubilized PGA more abundantly than 0,2% sarcosine. Conclusion: The solubilization technique of PGA expressed by E. coli proposed in this study is an alternative solution that can be considered for this purpose.